Hepatitis E virus exposure and risk factors among ethnic minority populations in Northern Vietnam - Vu Nhi Ha; Le Chi Cao; Tran Hai Dang; Dao Thi Huyen; Nguyen Tien Dung; Le Huu Song; Nguyen Linh Toan; Truong Nhat My; Thirumalaisamy P. Velavan (PLoS ONE, 2026)
Background Hepatitis E virus (HEV) causes sporadic outbreaks worldwide, with zoonotic and waterborne genotypes contributing to infections. In Vietnam, HEV genotypes 3 and 4 circulate among humans and swine, but data from remote, ethnic minority populations remain limited. Methods A cross-sectional study was conducted among 272 ethnic minority students at Thai Nguyen University of Medicine and Pharmacy (TUMP) to determine HEV infection markers and associated risk factors. Anti-HEV IgM and IgG were tested in serum samples using Wantai ELISA kits, and HEV RNA was detected by nested PCR targeting the ORF1 region. Demographic and exposure data were collected via structured questionnaires. Statistical analyses were performed using binary logistic regression. Results One participant (0.37%) tested positive for anti-HEV IgM, and 69 (25%) were positive for anti-HEV IgG, while HEV RNA was undetectable. HEV-IgG seroprevalence increased significantly with age (p = 0.004) but showed no sex-related differences. Consumption of tap or mixed water sources (p = 0.043) and raw or undercooked pork liver (p = 0.018) were significantly associated with HEV-IgG positivity. Multivariate analysis confirmed these factors as independent predictors of prior HEV exposure (adjusted OR = 1.6 and 4.8, respectively). Conclusions A moderate HEV seroprevalence among ethnic minorities indicates substantial prior exposure in northern Vietnam. Strengthening water sanitation, food safety awareness, and routine HEV surveillance is recommended to mitigate infection risk in vulnerable communities.